Physical excercise in the patient with renal failure - Javier Elicier Pereira-Rodríguez; Devi Geesel Peñaranda-Florez; Ricardo Pereira-Rodríguez; Pedro Pereira-Rodríguez; Juan Camilo Quintero-Gómez; Uriel Eduardo Flores-Posadas; Luis Alberto Marin-Herrera; Daniela del Carmen Luna-Martínez; Alfredo Cruz-Morales (Revista de Nefrología, Diálisis y Trasplante, 2019)
Kidney disease is a pathology where the kidneys are seriously damaged, generating alterations in the ability to filter toxins and other waste substances in the blood. The aim of this study was to evidence the effects and role of physiotherapeutic intervention in patients with kidney disease. A systematic review was conducted, with retrospective and descriptive analysis, of scientific articles published in indexed databases between January 2007 and November 2018. The search was performed for studies in the EBSCO, SciELO, MEDLINE, Medscape, PubMed databases, as well as in Central, EMBASE, REDALYC, DOAJ, OVID and several journals on the subject. The criteria for inclusion of studies were used for systematic reviews of the PRISMA Statement, and a risk-of-bias assessment was performed through the evaluation of the Cochrane Collaboration and the PEDro scale. 68,620 scientific articles were recovered before applying the corresponding filters. After that, 20 articles were obtained which support the existence of an improvement in the quality of life, strength, physical capacity, oxygen consumption, physical, mental and social well-being in patients with renal failure. The performance of physical exercise in patients with renal failure improves the physical, social and mental response, as well as the activities of daily living. These effects are the result of an evaluation, prescription and adequate monitoring of the exercise. Therefore, we conclude it is essential that a professional in physiotherapy should participate in the interdisciplinary team necessary for the treatment of kidney disease.